2019
DOI: 10.3390/toxins11030160
|View full text |Cite
|
Sign up to set email alerts
|

Natural Occurrence and Co-Contamination of Twelve Mycotoxins in Industry-Submitted Cool-Season Cereal Grains Grown under a Low Heat Unit Climate Condition

Abstract: This study aims to evaluate the prevalence of mycotoxins in industry-submitted cool-season barley and wheat grown under low heat unit climate conditions. Seventy-two barley samples and 83 wheat samples were submitted by producers and industry from May 2016 to May 2017. The concentrations of twelve common mycotoxins, including nivalenol (NIV), deoxynivalenol (DON), 3-acetyldeoxynivalenol (3-ADON), 15-acetyldeoxynivalenol (15-ADON), ochratoxin A (OTA), zearalenone (ZEN), α-zearalenol (α-ZAL), β-zearalenol (β-ZAL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 31 publications
2
15
1
Order By: Relevance
“…With regards to occurrence of native forms, DON, FBs, and ZEN showed the highest simulated potential co-occurrence value, and in particular, DON was more probable to be found in co-occurrence with FBs in maize and with ZEN in wheat. This finding is consistent with the results of a recent study conducted on Canadian cereal samples where the co-occurrence of DON and other Fusarium mycotoxins was frequently observed in wheat and barley [29].…”
Section: Discussionsupporting
confidence: 93%
“…With regards to occurrence of native forms, DON, FBs, and ZEN showed the highest simulated potential co-occurrence value, and in particular, DON was more probable to be found in co-occurrence with FBs in maize and with ZEN in wheat. This finding is consistent with the results of a recent study conducted on Canadian cereal samples where the co-occurrence of DON and other Fusarium mycotoxins was frequently observed in wheat and barley [29].…”
Section: Discussionsupporting
confidence: 93%
“…The unpacked tea samples are usually stored in bulk until being supplied to markets, the bulk storage facilitates moisture migration and as a result increases the chances of mold growth any mycotoxins production (Chen et al, 2018). The prevalence of aflatoxins in line with this study is already reported in various foodstuff of Pakistan, for instance, in milk samples (Ismail et al, 2016), in animal feed samples (Ismail et al, 2017), and in mother milk samples (Khan et al, 2018) indicating that the environmental conditions in Pakistan are quite favorable for the growth of fungus and the production of aflatoxins.…”
Section: Occurrence Of Aflatoxins In Non-branded and Branded Teasupporting
confidence: 77%
“…In a study on stored wheat, AFB 1 was detected in four wheat samples at levels above the European Commission regulatory limit of 2 ppb in grains for human consumption [ 35 ]. In a recent study, Shi et al [ 36 ] found that wheat samples grown under low heat unit climate conditions were not contaminated by AFB 1 .…”
Section: Resultsmentioning
confidence: 99%